Transcatheter aortic valve implantation via the superficial femoral artery: An underused access route?. Issue 4 (26th February 2018) - Saraf, Smriti; Cockburn, James; Alsanjari, Osama; Hildick‐Smith, David
Abstract: Common femoral arterial (CFA) access is the most commonly used access route for transcatheter aortic valve implantation (TAVI). In majority of cases, it is easily accessible percutaneously without requiring surgical cut down. However, in patients with high body mass index (BMI) or central obesity, it can be more than 8–10 cm below the skin making the procedure more technically demanding and satisfactory hemostasis more difficult to achieve. The superficial femoral artery (SFA) lies only a few centimeters distal to the CFA with little compromise on vessel caliber, yet can allow more suitable access in certain patients with a high BMI. We describe three cases in which SFA access was successfully used as the primary delivery route for TAVI.